Financial Inclusion Based on Fintech Lending (Peer to Peer Lending) in Indonesia - Pradana, Hasta Dwi; Hermajiwandini, Chandra Murti Dewi Widowati; Rahmawati, Dwi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the effect of fintech lending on the level of financial inclusion in Indonesia, considering the moderating roles of financial literacy and the Information and Communication Technology Development Index (IPTI). The research applies a mixed methods approach using a convergent parallel design. Quantitative analysis was conducted using panel regression data from 34 provinces in Indonesia for the period 2019-2022, while qualitative data were obtained through in-depth interviews with fintech lending users in two cities. The findings reveal that fintech lending significantly improves financial inclusion. However, financial literacy has a negative moderating effect on the relationship, suggesting that increased literacy may lead to more selective behavior in adopting fintech services. These findings highlight the importance of incorporating financial literacy and ICT infrastructure considerations into fintech policies to optimize its role in expanding financial inclusion.